In the Wake of the Karatepe Discoveries - Obermann, J.
1. Participles of the Yqtl Pattern Outside Phoenician — 2. The Synonyms *mērîḇ and yārîḇ in Hebrew — 3. On the Correspondence of Nominal y- and m- in General.